The Antibacterial and Anti-Inflammatory Potential of Cinnamomum camphora chvar. Borneol Essential Oil In Vitro - Shanshan Xiao; Hang Yu; Yahui Guo; Yuliang Cheng; Weirong Yao (Plants, 2025)
Cinnamomum camphora chvar. Borneol essential oil (BEO, 16.4% borneol) is a by-product obtained during the steam distillation process used to produce natural crystalline borneol (NCB, 98.4% purity). This study aimed to compare the antibacterial activity of BEO and NCB against Staphylococcus epidermidis, and to evaluate the anti-inflammatory effect of BEO in vitro. Minimum inhibitory concentrations (MICs), determined by broth microdilution, were identical for both BEO and NCB (0.5 mg/mL). Despite this, BEO exhibited stronger antibacterial activity, suggesting synergistic enhancement by other components. Mechanistic studies revealed that BEO disrupted the bacterial cell wall, causing leakage of nucleic acids and proteins, and ultimately bacterial death. In LPS-induced RAW 264.7 macrophages, BEO dose-dependently reduced the production of TNF-α, IL-1β, and IL-6 (r = −0.9847, −0.9456, −0.9315). Network pharmacology, combined with primary and secondary factor analysis, was employed to identify anti-inflammatory pathways and key active compounds. Borneol contributed over 50% to the anti-inflammatory effect, followed by β-caryophyllene, limonene, camphor, and γ-terpinene. These findings highlight the potential enhanced bioactivity of BEO due to multi-component synergy.